The Public's Foreign Aid Priorities: Evidence from a Conjoint Experiment. Issue 5 (September 2020) - Doherty, David; Bryan, Amanda Clare; Hanania, Dina; Pajor, Matthew
Foreign aid is one of the few areas where Americans say the government should spend less. We leverage a unique conjoint experiment to assess how characteristics of an aid package, as well as characteristics of the targeted country, affect public support. We find that people are far more inclined to support economic aid than military aid and are disinclined to provide aid to undemocratic countries. We also find that people are more averse to providing aid—particularly economic aid—to countries in the "greater Middle East" than those countries' other characteristics would suggest. These effects are comparable to those associated with substantial increases in the cost of the aid package, suggesting that public wariness of foreign aid is not rooted in a fundamental aversion to spending in this domain. Our findings offer new insights into the contours of public opinion regarding foreign aid.